Radiotherapy Protocol Deviations and Clinical Outcomes: A Meta-analysis of Cooperative Group Clinical Trials - Ohri, Nitin (Oxford University Press, 2013)
BACKGROUND: Noncompliance with radiotherapy (RT) protocol guidelines has been linked to inferior clinical outcomes. We performed a meta-analysis of cooperative group trials to examine the association between RT quality assurance (QA) deviations and disease control and overall survival (OS). METHODS: We searched MEDLINE and the Cochrane Central Register of Controlled Trials for multi-institutional trials that reported clinical outcomes in relation to RT QA results. Hazard ratios (HRs) describing the association between RT protocol noncompliance and patient outcomes were extracted directly from the original studies or calculated from survival curves. Inverse variance meta-analyses were performed to assess the association between RT QA deviations and OS. A second meta-analysis tested the association between RT QA deviations and secondary outcomes, including local or locoregional control, event-free survival, and relapse. Random-effects models were used in cases of statistically significant (P < .10) effect heterogeneity. The Egger test was used to detect publication bias. All statistical tests were two-sided. RESULTS: Eight studies (four pediatric, four adult) met all inclusion criteria and were incorporated into this analysis. The frequency of RT QA deviations ranged from 8% to 71% (median = 32%). In a random-effects model, RT deviations were associated with a statistically significant decrease in OS (HR of death = 1.74, 95% confidence interval [CI] = 1.28 to 2.35; P < .001). A similar effect was seen for secondary outcomes (HR of treatment failure = 1.79, 95% CI = 1.15 to 2.78; P = .009). No evidence of publication bias was detected. CONCLUSION: In clinical trials, RT protocol deviations are associated with increased risks of treatment failure and overall mortality.